Empowering TVET education – UMP’s main agenda - UMP, PNC (2019)
As a public university and a member of the Malaysia Technical University Network (MTUN), Universiti Malaysia Pahang (UMP) will continue to boost and strengthen the transformation agenda in the country’s Technical and Vocational Education and Training (TVET) in a move to turn Malaysia into a developed, high-income nation by 2050. UMP’s Board of Directors’ Chairman, Dato’ Sri Ibrahim Ahmad said TVET would produce a home-grown workforce needed by the industry and country to cater to the challenges expected in the Industrial Revolution 4.0.